Exponentially correlated Hylleraas-configuration interaction studies of atomic systems. II. Non-relativistic energies of the 1 S-1 through 6 S-1 states of the Li+ ion - Sims, James S.; Padhy, Bholanath; Ruiz, María Belén (International Journal of Quantum Chemistry, 2021)
The exponentially correlated Hylleraas-configuration interaction wave function (E-Hy-CI) is a generalization of the Hylleraas-configuration interaction (Hy-CI) in which the single r(ij) of an Hy-CI wave function is generalized to the generic type r(ij)(nu ij)e(-omega ijrij). This type of correlation has the right behavior both in the vicinity of the r(ij) cusp and as r(ij) goes to infinity; this work shows that wave functions containing both linear and exponential r(ij) factors converge more rapidly than either one alone for low-lying excited states of S-1 symmetry. E-Hy-CI variational calculations with up to 8568 configurations lead to a nonrelativistic energy of -7.2799 1341 2669 3059 6491 6759 hartree for the 1 S-1 ground state of the Li+ ion.
CRIS-Team WoS Importer:2021-10-29